THROUGH THE EYE OF THE TEACHER: MEMORIES OF AN ELETRONIC GAME BASED ACTIVITY - Ogando, Luciana Pereira; Santos, Tamara Afonso Dos (South American Journal of Basic Education, Technical and Technological, 2016)
This article aims to present reports of a continuing education course offered to future English teachers in the city of Rio Branco. The motivation for the development of the course came from an opportunity to share experiences of the course Trace Effects Online Teacher Training offered by the American English Institute in the College of Arts and Sciences at the University of Oregon (UO AEI). Based on social-interactional theory perspective in which knowledge is constructed in a social environment, the inclusion of the game in the classroom can develop collaboratively the construction of new knowledge on various subjects, and thus providing the student a cultural transformation (GEE, 2007; ALVES 2005 and others). In this bias, the report itself is to present the results of a resarch that can contribute to English teachers and trainees, favorable methods to the process of teaching and learning using technology in the classroom, believing that some foundations may be planted seeking to improve the training of teachers to deal with the use of this feature, especially the game Trace Effects, improving therefore their teaching practices.